Reproductive biology of Indian mackerel, Rastreliger kanagurta (Cuvier, 1816) in Takalar Coastal Waters, South Sulawesi - Mauli Kasmi; Syamsul Hadi; Wayan Kantun (Jurnal Iktiologi Indonesia, 2017)
The objective of this research is to observe reproductive biology of Indian mackerel in Takalar coastal waters through gonad maturity development, the first size of mature gonad, spawning, gonado somatic index (GSI), and fecundity. Sampling was done for eight months started from March to October 2015. Gonad maturity stage was observed morphologically, spawning season focusing on direct observation result toward gonad by identifying Indian mackerel which has spawned.GSI was analyzed based on comparison between gonad weight and Indian mackerel weight while fecundity was observed by gravimetric method. Analysis result shows that Indian mackerel gonad maturity throughout the year with peak occurring in July and August. GSI was around 0,928-4,490. The first size of gonad mature of female Indian mackerel is 21,18 cm and male Indian mackerel is 21,31 cm. Spawning occurs after peak of gonad maturity so next month, value of maturity index decreases slowly and gradually. Indian mackerel has total fecundity around 11.235- 40.878 granule. Abstrak Penelitian ini bertujuan untuk mengamati biologi reproduksi ikan kembung lelaki di perairan pesisir Takalar melalui perkembangan kematangan gonad, ukuran pertama matang gonad, musim pemijahan, indeks kematangan gonad (IKG), dan fekunditas. Pengambilan sampel dilakukan selama delapan bulan mulai Maret sampai Oktober 2015. Perkembang-an kematangan gonad diamati secara morfologi. Musim pemijahan mengacu pada hasil pengamatan langsung terhadap gonad dengan mendata ikan kembung lelaki yang telah memijah. IKG dianalisis berdasarkan perbandingan antara bobot gonad dan bobot tubuh ikan kembung lelaki, sedangkan fekunditas dihitung dengan metode gravimetrik. Hasil analisis menunjukkan bahwa ikan kembung lelaki mengalami kematangan gonad sepanjang tahun dengan puncak terjadi pada bulan Juli dan Agustus. IKG berkisar 0,928-4,490. Ukuran ikan kembung lelaki betina kali pertama matang gonad adalah 21,18 cm dan jantan adalah 21,31 cm. Pemijahan terjadi setelah puncak kematangan gonad sehingga pada bulan berikutnya terjadi penurunan nilai indeks kematangan secara perlahan dan bertahap. Ikan kembung lelaki memiliki fekunditas total berkisar 11.235-40.878 butir.